2019
DOI: 10.7555/jbr.32.20170099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restoration technique on resistance to fracture of endodontically treated anterior teeth with flared root canals

Abstract: This study was designed to compare the impact of post and core systems on resistance to fracture of endodontically treated anterior teeth with flared root canals and to assess their fracture pattern. Sixty central incisors were cut horizontally 2 mm coronal to the cementoenamel junction (CEJ). After root canal therapy, teeth were assigned into 6 groups ( n =10 each) based on a post system and used as follows: Group C, non-flared root received size #1 glass fiber posts (Control); Group AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 34 publications
(30 reference statements)
2
24
0
Order By: Relevance
“…It is imperative to highlight the increased fracture resistance that the CAD/CAM system provides to the root 6,38 , which supports the choice of this system in the present study. Moreover, the specimen survival rate in groups 2 and 3 was higher than that in group 1, i.e., there was less root fracture -except for the fracture of copings in specimens number 1 and 4 in groups 2 and 3, respectively -which is consistent with the results reported in other studies 5,6,39 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is imperative to highlight the increased fracture resistance that the CAD/CAM system provides to the root 6,38 , which supports the choice of this system in the present study. Moreover, the specimen survival rate in groups 2 and 3 was higher than that in group 1, i.e., there was less root fracture -except for the fracture of copings in specimens number 1 and 4 in groups 2 and 3, respectively -which is consistent with the results reported in other studies 5,6,39 .…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that CAD/CAM-fabricated intraradicular posts increase root fracture resistance, providing an alternative to the use of prefabricated and cast metal posts 5 . An in vitro study 6 compared the fracture resistance of flared canals restored with CAD/CAM post-and -core with prefabricated glass fiber and cast gold alloy posts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, regarding the teeth with large root canals ( 15 ), and bulk-fill composites properties ( 16 , 17 ), this study has proposed an experimental technique of customization and cementation of glass fiber posts using bulk-fill flowable composites. Therefore, the aim of the present study was to evaluate the bond-strength and internal adaptation of customized glass fiber posts using different bulk-fill flowable composites, customized glass fiber posts using conventional composite resin, and fiber posts with no customization.…”
Section: Introductionmentioning
confidence: 99%
“…Bubbles, cracks, and gaps are more likely to form in thick cement, creating a concentrated stress area and reducing bond strength. Several techniques have been proposed to solve this problem, including restoration of the root canal with composite resin to decrease canal width, direct and indirect anatomical shaping of fiber posts with a composite resin, and the use of accessory posts ( 13 , 14 , 18 , 21 ). Another technique proposed in the present study uses dual-cured core build-up composite resin instead of self-adhesive resin cement for simultaneous reinforcement and cementation of fiber posts to overflared canals.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that direct and indirect anatomic posts could be an alternative to cast metal post-and-cores during the treatment of overflared root canals ( 15 ). Some studies have recently proposed another method for relining and reinforcing weakened root canal walls with composite resin before fiber post cementation ( 10 , 17 , 18 ). Gomes et al .…”
Section: Introductionmentioning
confidence: 99%